ETHNO-EDUCATIONAL PROJECT «FUNDAMENTAIS OF THE MOUNTAIN FARMING OF THE HUTSUL REGION OF THE UKRAINIAN CARPATHIANS» - Zelenchuk, Ivan (Mountain School of Ukrainian Carpaty, 2019)
The article is devoted to the problem of preservation of Ukrainian ethno-cultural and historical heritage, which is especially relevant for the Hutsul region of Ukraine. Its socio-economic and environmental aspects are closely connected with everyday life and work of Hutsuls – one of the ethnographic groups of Ukrainians inhabiting the highland part of the Ukrainian Carpathians. In order to solve the problem of rational organization of labor of the Hutsul population in private households, primary agricultural education should be implemented. In our opinion, this should be a theoretical and a practical minimum of basic agricultural knowledge required for practicing mountain farming in the Ukrainian Carpathians that occupy a considerable part of the territory and are home to a large number of Ukrainian population. However, there are significant shortcomings of modern school education in this region: a large gap between theoretical knowledge gained at school and those practical tasks that need to be solved in everyday life; extremely low effectiveness of much of the outdated, scholastic school teaching methods. To overcome these shortcomings, the regional component of the educational content in Ukraine needs to be reformed substantially. One of the possible approaches to the practical solution of this problem is the author's ethno-educational project «Fundamentals of the mountain farming of the Hutsul region of the Ukrainian Carpathians». This project is thematically related to the urgent problem of updating the contents of education and teaching technologies in mountain village comprehensive educational institutions of Hutsulschyna. It may be a regional component of implementing the concept of profile education in mountain rural secondary schools of Ukraine.Due to this, graduates will be able to master the basics of traditional and modern subsidiary farming in mountainous conditions.The project contributes to the practical approximation of the regional component of the content of general secondary education to real life needs and interests of highlanders who remain to reside and work in their native land.